EFL in Primary Classrooms of Choco: A Challenge for In-service Teachers and Educational Authorities (2019)
The following study explored choices and methods to improve professional training and development among primary school teachers from Chocó in order to enhance English teaching at the basic school level. The research work was an analyticaldescriptive study undertaken with in-service primary school teachers from ChocóColombia. The investigation analyzed the situation faced by primary school teachers from Chocó when teaching EFL (English as a Foreign Language) in the primary school classroom. Furthermore, the study, to some extent, describes the existence of social, cultural, political and academic factors which may intervene in the EFL context of Chocó’s primary education as well. Both quantitative and qualitative research methods were applied in the development of the investigation. A questionnaire was implemented as the quantitative data collection instrument and the interview as the qualitative one. Additionally, classroom observation was also used as an instrument to gather data. The study has revealed that in-service primary teachers from Chocó lack the knowledge they need to teach English to young children as they are trained neither from a linguistic nor from a methodological point of view.